2023
DOI: 10.3390/jcm12175572
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Clinical Picture of Hospitalized Patients with COVID-19 between the Early and Late Period of Dominance of the Omicron SARS-CoV-2 Variant

Robert Flisiak,
Dorota Zarębska-Michaluk,
Krystyna Dobrowolska
et al.

Abstract: This study aimed to compare the clinical picture of COVID-19 in the initial and later period of Omicron dominance and to identify populations still at risk. A retrospective comparison of the clinical data of 965 patients hospitalized during the early period of Omicron’s dominance (EO, January–June 2022) with 897 patients from a later period (LO, July 2022–April 2023) from the SARSTer database was performed. Patients hospitalized during LO, compared to EO, were older, had a better clinical condition on admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Epidemiological analyses of various human populations confirmed that Omicron infections are characterized by decreased lower respiratory tract involvement, reduced odds of hospitalization due to severe COVID-19, and less mortality [74][75][76][77][78]. Despite the emergence of subsequent Omicron sublineages, such as BA.4/BA.5 and XBB, the hospitalization and death risk remained lower compared to previous SARS-CoV-2 variants, such as Delta [79][80][81][82].…”
Section: Omicron Lineage Is Milder But Not Negligiblementioning
confidence: 99%
“…Epidemiological analyses of various human populations confirmed that Omicron infections are characterized by decreased lower respiratory tract involvement, reduced odds of hospitalization due to severe COVID-19, and less mortality [74][75][76][77][78]. Despite the emergence of subsequent Omicron sublineages, such as BA.4/BA.5 and XBB, the hospitalization and death risk remained lower compared to previous SARS-CoV-2 variants, such as Delta [79][80][81][82].…”
Section: Omicron Lineage Is Milder But Not Negligiblementioning
confidence: 99%
“…To assess the burden of newly diagnosed HAV cases during the COVID-19 pandemic, we explored the pre-pandemic period, depending on the dominant variants of SARS-CoV-2 [ 19 , 20 , 21 ]. The pandemic period was divided into four periods: (i) the pre-Delta lineage period from March 2020 to June 2021, (ii) the Delta lineage dominance period from July 2021 to December 2021, (iii) the early phase of the Omicron SARS-CoV-2 lineage dominance from January 2022 to June 2022 (dominated by the BA.1 and BA.2 Omicron subvariants), and (iv) a later phase of Omicron SARS-CoV-2 dominance from July 2022 to December 2023 (characterized predominantly by the dominance of XBB and its descendent sublineage).…”
Section: Methodsmentioning
confidence: 99%
“…However, the actual number of infections and deaths associated with Omicron may be even higher. Possible reasons for this include the underdiagnosis of affected individuals and the failure to report new cases of the disease due to the WHO’s announcement that COVID-19 no longer constitutes a public health emergency of international concern [ 16 ].…”
Section: Introductionmentioning
confidence: 99%